Analysis Potential of Company Bankruptcy at PT. Gowa Makassar Tourism Development Tbk - Saiful; Muhammad Ilham Wardhana Haeruddin; Nurman; Anwar Ramli; Andi Mustika Amin (PT. Maju Malaqbi Makkarana, 2023)
Analysis of Company Bankruptcy Potential at PT. Gowa Makassar Tourism Development TBK. Thesis. Department of Management, Faculty of Economics and Business. Makassar public university. Supervised by Mr. Muhammad Ilham Wardhana Haeruddin and Mr. Nurman. This study aims to determine the potential for corporate bankruptcy at PT. Gowa Makassar Tourism Development Tbk Period 2017 to 2021. The type of research used is quantitative descriptive. The population in this study is the financial statements of PT. Gowa Makassar Tourism Development Tbk. The sample of this research is the income statement and balance sheet from the financial statements of PT. Gowa Makassar Tourism Development Tbk. 2017 to 2021. The data collection technique used is Documentation. Data analysis techniques are used to assess, identify, and explain the possibility of bankruptcy. The results of this study indicate the analysis of the level of bankruptcy of the modified Altman Z-score model of PT. Gowa Makassar Tourism Development TBK. the 2017-2021 period is categorized as being in good health or not bankrupt.